Menopause in women with chronic immunosuppressive treatment – how to help those patients - Cyganek, Anna; Pietrzak, Bronisława; Wielgoś, Mirosław; Grzechocińska, Barbara (Menopause Review/Przegląd Menopauzalny, 2016)
Women after organ transplantation with chronic immunosuppressive therapy or after bone marrow transplantation without such therapy are a growing group of patients. Although their problems in the peri- and postmenopausal period are the same as in healthy women, due to the primary disease and treatment applied they represent a huge challenge from the point of view of their hormonal treatment of menopause. Transplanted women have no particular contraindications for hormonal therapy use. General contraindications, however, such as arterial hypertension, thrombosis in medical history, diabetes, endometriosis, myomas, or active neoplastic disease, have a higher incidence in this group of patients than in healthy women, which significantly influences the possibility of using hormonal therapy. On the other hand, taking into consideration the predisposition for premature menopause in this group, in combination with chronic immunosuppression, it predisposes these patients for higher cardiovascular disease incidence and bone density loss, so hormonal therapy would be highly advisable. Therapy management in transplanted patients requires special care and close monitoring of the transplanted organ. Saving lives with organ transplantation is one of the greatest achievements of contemporary medicine. For long-term improvement of their quality of life, emphasis should be put on regular diagnostic examinations, early detection of abnormalities, and introduction of effective treatment.